The view from here: A woman early career endocrinologist in India - Lakshmi Nagendra (Indian Journal of Endocrinology and Metabolism, 2023)
Being a young female endocrinologist and a new mother brings its own challenges. As much as an understanding family helped me deal with the myriad of things at home, equally understanding colleagues and the huge network of endocrine fraternity provided me the much-needed support professionally. From helping me juggle my responsibilities, to answering all my questions about complex endocrine disorders, the close-knit endocrine fraternity in India has been my greatest source of strength. I am sure my story and experiences will inspire many more women to be part of this wonderful fraternity.